2019
DOI: 10.1029/2019ms001728
|View full text |Cite
|
Sign up to set email alerts
|

New Bidirectional Ammonia Flux Model in an Air Quality Model Coupled With an Agricultural Model

Abstract: Ammonia surface flux is bidirectional; that is, net flux can be either upward or downward. In fertilized agricultural croplands and grasslands there is usually more emission than deposition especially in midday during warmer seasons. In North America, most of the ammonia emissions are from agriculture with a significant fraction of that coming from fertilizer. A new bidirectional ammonia flux modeling system has been developed in the Community Multiscale Air Quality (CMAQ) model, which has close linkages with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 90 publications
0
54
0
Order By: Relevance
“…Despite the tendency to be lower than the reported usage, simulated demand‐based inorganic fertilization for 2011 at the county level follows the agricultural land distribution better than USGS sales‐based usage. Integrated air quality modeling is demonstrated for 2011 over the same domain using CMAQ configured with a bidirectional NH 3 modeling approach that directly uses EPIC‐simulated soil properties including soil NH 3 content (Pleim et al, ). With spatially and temporally better represented soil NH 3 information from EPIC and consequently improved representation of land‐atmosphere NH 3 flux, CMAQ shows better performance in simulating gas‐phase NH 3 and NH 4 + wet deposition in comparison to the traditional approach based on NH 3 emission estimates solely from fertilizer sales data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the tendency to be lower than the reported usage, simulated demand‐based inorganic fertilization for 2011 at the county level follows the agricultural land distribution better than USGS sales‐based usage. Integrated air quality modeling is demonstrated for 2011 over the same domain using CMAQ configured with a bidirectional NH 3 modeling approach that directly uses EPIC‐simulated soil properties including soil NH 3 content (Pleim et al, ). With spatially and temporally better represented soil NH 3 information from EPIC and consequently improved representation of land‐atmosphere NH 3 flux, CMAQ shows better performance in simulating gas‐phase NH 3 and NH 4 + wet deposition in comparison to the traditional approach based on NH 3 emission estimates solely from fertilizer sales data.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the system has gone through many updates and advances to the current release of CMAQv5.3 (https://github.com/USEPA/CMAQ). Different from the previous bidirectional NH 3 approach using the fertilization information to simulate soil NH 3 in CMAQ, a new approach of bidirectional flux modeling, which directly uses EPIC‐simulated soil properties including soil NH 3 concentration (Pleim et al, ), is implemented in the current release of CMAQ. The new approach directly follows the bidirectional flux box model based on field studies demonstrated by Pleim et al () and has additional updates to some key parameterizations.…”
Section: Integrated Modeling and Evaluationmentioning
confidence: 99%
“…The CrIS NH3 product can be used for many applications such as monitoring, air quality model evaluation (e.g. Whaley et al, 2018;Pleim et al, 2019), dry deposition estimates , and emissions estimates for larger agriculture sources, industrial point sources (Dammers et al, 2018), and wildfires (Adams et al, 2019). Here we provide examples that demonstrate and expand upon these applications.…”
Section: Application Examplesmentioning
confidence: 90%
“…vegetation) can be re-released into the atmosphere later depending on the ammonia balance between the air and leaf apoplastic concentrations (compensation point) (do that there is bi-directional flow) (e.g. Massad et al, 2010;Bash et al, 2013;Pleim et al, 2019). fires) overlaid in red.…”
Section: Dailymentioning
confidence: 99%
See 1 more Smart Citation